A fluorogenic probe targeting two spatially separated enzymes for selective imaging of cancer cells. Issue 25 (10th March 2022) - Park, Sang-Hyun; Jung, Hyoje; Kim, Yujun; Shin, Injae
Abstract : We describe a fluorogenic probe BocLys(Ac)-AB-FC targeting both histone deacetylases (HDACs) and cathepsin l, which are overexpressed in spatially separated subcellular organelles of cancer cells. Abstract : We describe a fluorogenic probe BocLys(Ac)-AB-FC targeting both histone deacetylases (HDACs) and cathepsin l, which are overexpressed in spatially separated subcellular organelles of cancer cells. The results show that this fluorogenic probe can be used for selective cancer cell imaging without interference arising from normal cells.